Composite Coatings with Liposomes of Melissa officinalis Extract for Extending Tomato Shelf Life (2024)
In this study, active coatings based on carboxymethylcellulose (CMC) were prepared using liposomes filled with an aqueous extract of Melissa officinalis retained in high acyl gellan gum (HAG), low acyl gellan gum (LAG), and their mixture (HAG/LAG). The objective was to investigate the effect of these coatings on postharvest preservation of tomato (Solanum lycopersicum) fruits. The tomato fruits were divided into four groups: (i) coating with HAG-based liposomes (WL-HAG), (ii) coating with LAG-based liposomes (WL-LAG), (iii) coating with HAG/LAG-based liposomes (WL-HAG/LAG), and (iv) control group treated with sterile water. Over a period of 10 days, various quality attributes, such as respiration rate, soluble solids, titratable acidity, luminosity, weight loss, malondialdehyde (MDA) content, hydrogen peroxide, total phenols, and DPPH scavenging ability, were studied. The results indicated that the WL-HAG coatings significantly (p < 0.05) decreased the respiration rate, hydrogen peroxide, and MDA content compared to the control fruits and other coatings. Therefore, WL-HAG could be considered a promising option to enhance postharvest preservation of tomato fruits in the Colombian fruit and vegetable industry.